The growth and post harvest performances of different species of oyster mushroom (Pleurotus sp.) cultivated on sawdust and oil palm frond - Zairul-Fazwan, M.Z.; Aziz, A.; Cha, T.S. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Oyster mushrooms (Pleurotus sp.) have more than 1000 species worldwide such as grey (Pleurotus sajor-caju), yellow (P. citrinopealatus), pink (P. flabellatus) and white (P. florida) which are cultivated on various agricultural wastes. In this study, the growth performance, yield and postharvest quality of different species of oyster mushroom cultivated on sawdust and oil palm frond (OPF) were determined. Sawdust and OPF in combination with rice bran and calcium carbonate in 100:10:1 ratio respectively was used as substrates. The growth performance in terms of mycelium growth, days for mycelium to fill up the bag, pinhead emergence and fruiting body formation were measured. The postharvest qualities studied involved color, texture, moisture, ash, protein and crude fiber contents. Yellow oyster mushroom on OPF took the shortest time for mycelium growth, mycelium fill up the bag, pinhead emergence and fruiting body formation. However, oyster mushrooms cultivated on sawdust had higher biological efficiency (29.34 to 60.76%) as compared to on OPF (21.49 to 45.08%). White oyster mushroom had the highest biological efficiency followed by yellow, grey and pink. Meanwhile, grey oyster mushroom showed darker color compared to other oyster mushroom species. OPF used as substrates provide brighter yellow and pink color in yellow and pink oyster mushrooms respectively and greater in firmness especially for pink oyster mushroom. There was no significant difference (P>0.05) found in chemical properties of different oyster mushroom species cultivated on sawdust and OPF. In conclusion, oyster mushrooms cultivated on sawdust produced better yield even though OPF gave better growth performance and physical properties of color and firmness.